2013
DOI: 10.1155/2013/495814
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Zalcitabine in Medicaments by Differential Pulse Voltammetry

Abstract: The zalcitabine (ddC) has been extensively used in the treatment of HIV patients due to its antiretroviral activity. The quality control of this active principle in medications is of outstanding importance to public health. The principal objective of the current study was the development of an alternative analytical methodology for the zalcitabine determination using a voltammetric process. The zalcitabine gives a reduction peak (at −1.22 V versus Ag/AgCl) at the hanging mercury drop electrode (HMDE). The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The SLN formulation composed of surfactant poloxamer 188 shows better drug release as compared with formulation with Tween 80. This might be due to the higher HLB value of Poloxamer 188 [< 24] than Tween 80 [6]. Hence, it might be concluded that the higher the percentage of the surfactant, the higher will be the degree of drug release [111].…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%
“…The SLN formulation composed of surfactant poloxamer 188 shows better drug release as compared with formulation with Tween 80. This might be due to the higher HLB value of Poloxamer 188 [< 24] than Tween 80 [6]. Hence, it might be concluded that the higher the percentage of the surfactant, the higher will be the degree of drug release [111].…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%